Healthcare benefits linked with Below Poverty Line registration in India: Observations from Maharashtra Anaemia Study (MAS) - Ahankari, Anand; Fogarty, Andrew; Tata, Laila; Myles, Puja R. (F1000Research, 2017)
A 2015 Lancet paper by Patel et al. on healthcare access in India comprehensively discussed national health programmes where some benefits are linked with the country’s Below Poverty Line (BPL) registration scheme. BPL registration aims to support poor families by providing free/subsidised healthcare. Technical issues in obtaining BPL registration by poor families have been previously reported in the Indian literature; however there are no data on family assets of BPL registrants. Here, we provide evidence of family-level assets among BPL registration holders (and non-BPL households) using original research data from the Maharashtra Anaemia Study (MAS). Social and health data from 287 pregnant women and 891 adolescent girls (representing 1178 family households) across 34 villages in Maharashtra state, India, were analysed. Several assets were shown to be similarly distributed between BPL and non-BPL households; a large proportion of families who would probably be eligible were not registered, whereas BPL-registered families often had significant assets that should not make them eligible. This is likely to be the first published evidence where asset distribution such as agricultural land, housing structures and livestock are compared between BPL and non-BPL households in a rural population. These findings may help planning BPL administration to allocate health benefits equitably, which is an integral part of national health programmes.